DISTRIBUSI HASIL TCM TERDUGA TUBERKULOSIS DI UPT PUSKESMAS KRAGILAN BERDASARKAN DURASI MEROKOK DAN NILAI CARDIOTHORATIC RATIO - Larasati Puspa Amalia; Yusianti Silviani (LPPM Universitas Abdurrab, 2026)
Tuberculosis (TB) remains a global health problem, particularly in developing countries such as Indonesia. TB diagnosis can be performed using Rapid Molecular Tests supported by radiological examinations such as the Cardiothoracic Ratio (CTR). Additionally, smoking is a risk factor that can increase susceptibility to TB infection. This study aims to determine the distribution of TCM results in patients suspected of having tuberculosis based on smoking duration and CTR values. This study used a descriptive observational design with a retrospective approach. The study sample consisted of 72 patients suspected of having tuberculosis at the UPT Puskesmas Kragilan who had undergone TCM and X-ray examinations. Data were analyzed descriptively in the form of frequency distributions and percentages. The results showed that 23.6% of patients had positive TCM results and 76.4% had negative results. Based on smoking duration, the passive smokers group had the highest positive percentage (9.7%), followed by >10 years (8.3%) and <10 years (5.6%). Based on CTR values, all positive TCM results were found in the CTR <0.5 group.The conclusion of this study indicates that there is variation in the distribution of TCM results based on smoking duration but does not show a consistent pattern of increase. CTR values do not show a direct association with TCM results.